The Relation of Sleep Quality in Pregnant Mothers with The Incidence of Preeclampsia - Miftahul Hasanah; Dwi Estuning Rahayu; Rahajeng Siti Nur Rahmawati (Journal of Ners and Midwifery, 2022)
The main focus in pathogenesis of disease is the state of wakefulness with little attention regarding the state of sleep. Whereas, sleep is active condition where metabolism, memory consolidation, tissue restoration and homeostatic balance are maintained. Bad sleep quality had impact on human health, especially caused some complications in pregnancy. This study was aimed to know the relation of sleep quality in pregnant mother with the incidence of preeclampsia in Gambiran Hospital Kediri. Analytical survey method with cross sectional study was performed on 30 respondents who complied inclusion and exclusion criteria. The Pittsburgh Sleep Quality Index (PSQI) was used in determined sleep quality. The result of Chi Square test with Î± = 0.05 and df = 1 was clarified that the score of Ï‡2count (8.56) > Ï‡2table (3.841) which meant H0 was rejected and Ha was accepted. Based on the result, there was relation of sleep quality in pregnant mothers with the incidence of preeclampsia in Gambiran Hospital Kediri.